REINTERPRETASI KONSEP ISLAM KAFFAH PERSPEKTIF FAKHRUDDIN AL-RAZI : (Aplikasi Teori Hermeneutika Hans-Georg Gadamer) - Mila Aulia; Moh. Nurun Alan Nurin Perdana Kusuma; Roudlotul Jannah (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
The existence of hermeneutics in turn has a major influence on the development of a multi-interpretative world of interpretation. Hans-Georg Gadamer’s theory is used to interpret the Koran through its hermeneutical style of thinking which has a philosophical-productive nuance. Meanwhile, Fakhruddin al-Razi is a popular interpretation scholar who often carries out theological debates among rationalists and traditionalists through his logical ideas. This study departs from the concept of Islam kaffah which is warmly echoed by religious activists as a theological discourse to welcome Muslims to return to "complete Islam". To reveal a message that is more meaningful than the literal meaning of Islam kaffah, the purpose of this study begins by elaborating the basic theories of Hans-George Gadamer’s hermeneutics, then using them as an analytical knife in reading the concept of Islam kaffah from the perspective of Fakhruddin al-Razi in Q.S al-Baqarah [2]: 208. This type of study is qualitative with a literature approach. The data collection method uses documentation techniques, while the data analysis method uses a philosophical approach. The resulting meanings include a sign to leave sin and immorality, the word al-silmi means the state of a servant who is pleased and does not feel heavy-hearted about the destiny that has been set by Allah, and finally the general meaning of the verse is to stay away from anger and revenge.